Thandeka Mfinyongo and Dr. Katharina Greven about indigenous Xhosa music - Mfinyongo, Thandeka; Greven, Katharina (Cluster Conversations, 2025)
In this latest episode of the Cluster Conversations, artist fellow Thandeka Mfinyongo talks with her host Dr. Katharina Greven about her recent residency with the Cluster of Excellence in Bayreuth. During her stay, Thandeka Mfinyongo was working on her project “Ingoduko” which she considers a sort of homecoming and an appreciation of African music – her music encapsulates where it began and a nostalgia of home. It is a musical performance celebrating our culture and giving a voice to the Xhosa indigenous instruments, uhadi (gourd bow) and umrhubhe (mouth bow). While in Bayreuth she gave workshops and concerts to teach indigenous music to young people and anyone interested.